TcO2 oxidative dissolution by birnessite under anaerobic conditions: a solid–solid redox reaction impacting the environmental mobility of Tc-99 - Stanberry, Jordan; Szlamkowicz, Ilana; Purdy, Lauren R; Anagnostopoulos, Vasileios (Environmental science--processes & impacts, 2021)
Remediation efforts for the abatement of Tc-99 contamination in the environment have traditionally focused on the reduction of soluble pertechnetate (Tc(vii)O4−) to insoluble, and less mobile, technetium(iv) oxide (TcO2). Effectiveness of the reductive immobilization of Tc-99 depends on the susceptibility of TcO2 to oxidation to TcO4−in situ, as it is subject to dissolution by oxidizing agents, such as oxygen. Manganese minerals can be a liability for the long-term in situ immobilization of Tc-99, even in suboxic and anoxic systems due to their strong oxidizing capacity. This study presents for the first time the oxidative dissolution of TcO2 to pertechnetate by birnessite under anaerobic conditions. Oxidative dissolution of TcO2 was studied as a function of pH and birnessite:TcO2 ratios and in the presence of Ca2+ and Mn2+. As low as 5 mg of birnessite dissolved ∼65% of the original TcO2 in the suspensions and subsequently released TcO4− in the aqueous phase at both pH 6.5 and 8 in the absence of oxygen. On the other hand, the ability of birnessite to sequester calcium and manganese on its surface at pH 6.5 through sorption was shown to inhibit the oxidative capacity of birnessite. Maximum TcO4− release in the aqueous phase by Ca- and Mn-loaded birnessite was ∼50% less compared to pure birnessite, indicating that divalent cations sorb on active centers responsible for birnessite's oxidative capacity and potentially passivate the mineral. In summary, birnessite exerts strong geochemical controls over the mobility of Tc-99 in anoxic systems by oxidatively mobilizing the otherwise insoluble Tc(iv) to Tc(vii) and their presence in natural systems needs to be taken into account when long-term remediation strategies are being designed.